Physical and performance characteristics of Japanese Division 1 collegiate football players - Iguchi, J.; Yamada, Y.; Ando, S.; Fujisawa, Y.; Hojo, T.; Nishimura, K.; Kuzuhara, K.; Yuasa, Y.; Ichihashi, N. (The Journal of Strength and Conditioning Research, 2011)
This study aimed to establish the physical and performance characteristics of football players in the Japanese Division 1 collegiate football program and perform a comparison of these characteristics between Japanese (n = 208) and US Division 1 football players (n = 797). The following comparisons were made: (a) between a higher-ranked university team vs. a lower-ranked university team in Japan, (b) between different playing positions in Japan, (c) between starters and nonstarters in Japan, and (d) between playing positions in Japan vs. those in the United States. The results of this study suggest that players in the higher-ranked university team were heavier, stronger in back squat, jumped higher, and had greater power than those on the lower-ranked team. Furthermore, linemen were generally characterized by larger size, greater strength, and more fat as compared with backs. On the other hand, backs tended to be faster, smaller in physical size, have higher vertical jump height, and show greater relative strength than linemen did. Starters were taller, heavier, stronger, had more powerful, and more fat-free mass than nonstarters. Finally, our results revealed that players in the United States were superior to players in Japan in all body status comparisons (p < 0.01). This study revealed that performance and superior body composition are essential for the success of a football player. Power and strength seem to be key factors in defining good football performance.